PENENTUAN FAKTOR- FAKTOR PENGHAMBAT KEBERHASILAN SISWA SEKOLAH DASAR DALAM UJIAN AKHIR SEKOLAH BERSTANDAR NASIONAL - Yusuf, Ridwan (IIB Darmajaya, 2012)
Association rule derivation has a role play in decision making process. The important step of Association rule derivation is identify the frequent item set, and make the association theorem of that item set. Association rule used to describe relation between the items in transactional data table or relational data. This research is done on purpose to find out the inhibiting factors ofÂ national standard final exam of the student in elementary school (UASBN). The inhibiting factors are determined by seeing data relation of UASBN result in Metro city, the school status, student background and also their condition using association rule apriori algorithym method. Association rule method in this research use the minimum support 33% or 0.33 and minimum confidence 75% atau 0.75. As the result, it will be the inhibiting factors of national standard final exam of The student in elementary school.There are 3 factors, 1) School status, 2) Studentsâ Parentsâ Occupation, 3) Studentsâ Parentsâ salary. Â Key word : UASBN, frequent, item set, association rule.